PENGARUH KOMITMEN DAN KEPUASAN TERHADAP LOYALITAS KONSUMEN MELALUI KEPERCAYAAN DALAM MENGGUNAKAN PRODUK JASA TITIP TOKO ONLINE - Muhamad Rifa'i; Wisari Yati; Riski Aprilia Dwi Susanti (Unitri Press, 2020)
The purpose of this research is to know and analyze: the influence of commitment to consumer confidence, the influence of satisfaction on trust, the influence of commitments that affect consumer loyalty, the influence of consumer satisfaction on loyalty, the influence of confidence in consumer loyalty, influence of consumer commitment to consumer loyalty through consumer confidence, and influence consumer satisfaction on loyalty through consumer confidence. The research population is a student in Malang City with sample of 91 respondents with judgmental sampling technique. The data used by the primary data collected through questionnaires, for the analysis of the data used is path analyisis. The results showed that consumer commitment was influential towards consumer confidence, satisfaction was influential in trust, a commitment to influence loyalty, customer satisfaction was influential towards loyalty, trust in loyalty, an influential commitment to loyalty through trust and satisfaction impacting loyalty through trust.